Characterization of carbon based nanostructures for the detection of tuberculosis - Muñante Palacin, Paulo Edgardo (2017)
Tuberculosis is a leading killing disease worldwide with more than 9 million people a ected per year. Current diagnostic methods exhibit several disadvantages; one of the most promising alternatives to overcome this is the development of nanostructured diagnostic systems which are able to detect molecules associated with certain diseases. Graphene since its discovery has been the focus for the development of these sensing elements due to its excellent electronic properties. In this work, a graphene-based eld e ect transistor (FET) has been developed for tuberculosis DNA detection, in order to set the basis for a diagnostic method that overcomes current limitations. The sensing elements composed of graphene monolayers were manufactured in the stages of annealing of the substrate, addition of the linker and functionalization with the addition of a probe DNA for tuberculosis detection. Additionally, two conditions for the sensing element were generated; one with the addition of a complementary DNA sequence (\DNA Target") and the other with a mismatched DNA sequence (\Non-complementary DNA"). The graphene and the transistor, in each stage of the manufacturing process, were structural, chemical and morphologically characterized by Raman Spectroscopy, Energy Dispersive X-ray Spectroscopy (EDS), Optical Microscopy, Laser Scanning Microscopy (LSM), Scanning Electron Microscopy (SEM) and Atomic Force Microscopy (AFM). The results indicated an appropriate functionalization of the graphene surface with the linker, the immobilization of the probe tuberculosis DNA and the hybridization with the corresponding \DNA Target", demonstrated by observation of di erent homogeneous morphologies and an appropriate increase in the roughness in each stage of the manufacturing process. Also by the presence of characteristic peaks of nitrogenous bases and in the variation of graphene bands in the Raman spectrum. On the contrary, the sensor element with the \Non-complementary" showed an agglomeration of the molecules and segregation of salts on a heterogeneous surface. The results of the characterization are consistent with the electronic characteristics previously determined. This investigation contributes to a basis for the development of a tuberculosis detection system based on nanotechnology for clinical application.